KAJIAN LITERATUR MANAJEMEN PUBLIC RELATIONS DALAM MENGATASI PROBLEM SOLVING PADA PENGUSAHA UMKM DI PEKANBARU - Usman Usman; Firdaus El Hadi; Sartika Sartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The rise of locally owned UMKM businesses has its own efforts and strategies in running its business. Therefore, this study examines UMKM in Pekanbaru using a qualitative descriptive research method with a literature review approach, using observation, documentation, and literature data collection techniques with SWOT analysis as one of the solutions to find problem solving. Through an intrinsic case study, researchers are interested in studying four UMKM business cases in Pekanbaru as literature review material in a SWOT analysis using the SWOT Matrix as a tool to analyze the cases faced by the four UMKM businesses. The four businesses are: Cafe Jayuanji, RR Cafe, Sambal Coel, and Ampera Pondok Serasi. Where the results of the study were found through a SWOT analysis with the help of the SWOT Matrix to have different strengths, weaknesses, opportunities, and threats between the four UMKM businesses.Keywords: Management, Public Relations, Problem Solving, Business